Understanding the factors that influence matriculation and persistence in Black medical students - Mincey, Krista D.; Richardson, Briana S. L.; Johnson, Raymond O.; Heraut, Mary L. (Frontiers in Medicine, 2023)
Purpose: The Association of American Medical Colleges’ (AAMC) Strategic Plan lists ten action plans one of which is focused on understanding how systemic barriers, such as racism and access to quality education, may negatively impact diversity in academic medicine. Thus, the purpose of this study was to understand the factors that impact the matriculation and persistence of Black medical students. Method: A qualitative phenomenological study using Tinto’s Model of Institutional Departure as an organizing framework was used for this study. Participants were asked a series of questions covering topics related to their goals, their medical school experience, their preparation for medical school, what could improve their medical school experience, and advice for future Black medical students. Results: 40 in-depth semi-structured interviews were conducted during the fall 2022 term from October to December with Black medical students enrolled in over 16 US or Caribbean medical schools. Findings reported that two factors impacted matriculation for Black medical students (exposure to the medical field and resources, particularly financial resources). Findings also reported that three factors impacted the persistence of Black students once in medical school (diversity, support, and emotional resources). Conclusions: The five factors identified by participants that impact matriculation and persistence for Black medical students can be used by medical schools to increase their enrollment and graduation of Black students.